Automatic Video Summarization Using HEVC and CNN Features - Issa, Obada (2022)
A Master of Science thesis in Computer Engineering by Obada Issa entitled, “Automatic Video Summarization Using HEVC and CNN Features”, submitted in November 2022. Thesis advisor is Dr. Tamer Shanableh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).